RE-ENGINEERING HUMAN RESOURCE MANAGEMENT IN ARCHITECTURE EDUCATION: A SWOT ANALYSIS IN THE AGE OF NEP 2020 - Gaurish Chandawarkar, (IJRDO - Journal of Social Science and Humanities Research, 2025)
Re-engineering the Human Resource Management (HRM) in architectural education is a paradigm shift of the administrative control to participatory control in the vision of the National Education Policy of India (NEP) 2020. The paper examines the HRM in the light of governance based on a SWOT review of how architecture institutions can become decentralized, accountable, and sustainability oriented. Using Indian policy documents, literature in the field of human resource, and institutional frameworks, the analysis indicates that proper planning of human capital enhances institutional autonomy and is aligned with the overall objectives of the local self-government. Regulatory clarity, multidisciplinary expertise, and emerging digital practices are the main strengths, and the weaknesses are associated with bureaucratic inertia, the lack of HR data systems, and limited leadership mobility. The potential opportunities, including AI-based HR analytics, Green HRM, and partnership governance with urban organizations, suggest the presence of the innovation and community interactions, whereas weaknesses are still present in implementation gaps and talent retention. The strategic foresight model is offered in 2035 focusing on the predictive HR planning, continuous learning ecosystems, and governance audits as the instruments of institutional resilience. The results emphasize the fact that HRM is ceasing to be a support department but the processes heart of educational governance, which is sustainable, efficient, and transparent. Architecture education can be the backbone of Viksit Bharat 2047 by embedding the principles of ethical management and civic accountability into the affairs of institutional organizations, creating autonomous and inclusive institutions in harmony with the vision of India development.